Lyubov Mandzyuk: a creative portrait of a bandur player in ontophenomenological contours - Melikhova, Yulia (Часопис Національної музичної академії України ім.П.І.Чайковського, 2024)
Lyubov Mandzyuk is an iconic figure in academic bandura performance and modern Ukrainian art history. The author examines the peculiarities of the ontological and phenomenological essence of the artist's creative personality. It was determined that the creation of a life-creating portrait makes it possible to form a holistic image of a person by reflecting the intentional nature of his consciousness, the uniqueness of being in creativity, the strategy of selfrealization, worldview guidelines, the culture of thinking, feelings and behavior. An attempt was made (on the basis of reflexive explorations of interdisciplinary discourse, namely Husserlian and Sartrean methods) to produce a creative portrait of Lyubov Mandzyuk in ontophenomenological contours.The multi-faceted semantics of the creative portrait of the artist is substantiated in the psychological dimension (teleonomy as the actualization of personal potential, directing it to selfrealization through contextuality, panoramic thinking, intentionality and creative adaptation), cultural dimension (realization of the creative potential of the individual in the space of Ukrainian national culture, where the artist reproduces and interprets identity socio-cultural, value-content and social-educational experience in the context of the well-known triad "art-personality-society"); philosophical (the existence and co-existence of a creative personality as a subject of unique activity in the structure of a holistic worldview system and his ability to make a conscious choice). The influence of contextuality, openness and panoramic thinking on the teaching, research and organizational and educational activities of Lyubov Mandzyuk was revealed. It has been proven that self-actualization and realization of personal potential, orientation of socio-psychological guidelines for activities on a harmonious worldview and self-perception, beauty and perfection, love and kindness determine the level of spirituality of an individual as an existential embodiment in the culture of his thinking, feelings and behavior of altruistic value orientations and guidelines. The specifics, patterns of functioning and prerequisites for the conscious formation of the personal sense-life space of Lyubov Mandzyuk as the basis of her full self-realization are traced